Atlee Pine : A Minute to Midnight - Book 2 Book 2 - Baldacci, David (New York : Grand Central Publishing, 2019)
"FBI Agent Atlee Pines life was never the same after her twin sister Mercy was kidnapped--and likely killed--thirty years ago. After a lifetime of torturous uncertainty, Atlees unresolved anger finally gets the better of her on the job, and she finds she has to deal with the demons of her past if she wants to remain with the FBI. Atlee and her assistant Carol Blum head back to Atlees rural hometown in Georgia to see what they can uncover about the traumatic night Mercy was taken and Pine was almost killed. But soon after Atlee begins her investigation, a local woman is found ritualistically murdered, her face covered with a wedding veil--and the first killing is quickly followed by a second bizarre murder. Atlee is determined to continue her search for answers, but now she must also set her sights on finding a potential serial killer before another victim is claimed"--Publisher marketing.
Keywords: United States. -- Federal Bureau of Investigation -- Officials and employees; Fiction; Twin sisters -- Fiction; Serial murderers -- Fiction; Murder -- Investigation; Fiction; Small cities -- Georgia; Fiction; Secrecy -- Fiction; Cold cases (Criminal investigation) -- Fiction; Georgia -- Fiction; Detective and mystery fiction; Thrillers (Fiction)